Design and Implementation of an Embedded NIOS II System for JPEG2000 Tier II Encoding. (19th June 2013) - McNichols, John M.; Balster, Eric J.; Turri, William F.; Hill, Kerry L.
Abstract : This paper presents a novel implementation of the JPEG2000 standard as a system on a chip (SoC). While most of the research in this field centers on acceleration of the EBCOT Tier I encoder, this work focuses on an embedded solution for EBCOT Tier II. Specifically, this paper proposes using an embedded softcore processor to perform Tier II processing as the back end of an encoding pipeline. The Altera NIOS II processor is chosen for the implementation and is coupled with existing embedded processing modules to realize a fully embedded JPEG2000 encoder. The design is synthesized on a Stratix IV FPGA and is shown to out perform other comparable SoC implementations by 39% in computation time.